2020
DOI: 10.1101/2020.11.16.20232835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Convalescent COVID-19 patients are susceptible to endothelial dysfunction due to persistent immune activation

Abstract: The rapid rise of coronavirus disease 2019 patients who suffer from vascular events after their initial recovery is expected to lead to a worldwide shift in disease burden. We aim to investigate the impact of COVID-19 on the pathophysiological state of blood vessels in convalescent patients. Here, convalescent COVID-19 patients with or without preexisting conditions (i.e. hypertension, diabetes, hyperlipidemia) were compared to non-COVID-19 patients with matched cardiovascular risk factors or healthy participa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 70 publications
1
44
0
1
Order By: Relevance
“…Our results also underscore the potential role of endothelial cells in coagulation activation based on a positive correlation of D-dimer with angiopoietin-2 and multiple others endothelial cell markers (angiopoietin-1, P-selectin, thrombomodulin, TFPI, vWF:Ag, vWF:RCo, t-PA, P-selectin). In addition, the significance of microvascular damage is highlighted by other markers of endothelial cell activation and angiogenesis, the presence of circulating endothelial cells, and an association of endothelium activation with disease severity including respiratory and multiorgan failure [10À15,11À13, 61,63]. Moreover, it is congruent with a pathologic process affecting endothelial cells given the vast surface it occupies estimated in more than 1000 m 2 , or 10 12 endothelial cells (there are » 10 10 blood monocytes) weighting in excess of 100 gs in the adult human [64].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also underscore the potential role of endothelial cells in coagulation activation based on a positive correlation of D-dimer with angiopoietin-2 and multiple others endothelial cell markers (angiopoietin-1, P-selectin, thrombomodulin, TFPI, vWF:Ag, vWF:RCo, t-PA, P-selectin). In addition, the significance of microvascular damage is highlighted by other markers of endothelial cell activation and angiogenesis, the presence of circulating endothelial cells, and an association of endothelium activation with disease severity including respiratory and multiorgan failure [10À15,11À13, 61,63]. Moreover, it is congruent with a pathologic process affecting endothelial cells given the vast surface it occupies estimated in more than 1000 m 2 , or 10 12 endothelial cells (there are » 10 10 blood monocytes) weighting in excess of 100 gs in the adult human [64].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the impact of SARS-CoV-2, many studies have looked at the physiological responses the virus 1–4,19 . In this work, we sought to identify how specific SARS-CoV-2 proteins affect the vasculature by assessing the effect of individual SARS-CoV-2 proteins on endothelial cells (HUVEC).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we decided to focus on individual proteins, and allow further studies to pursue any combinations of interest. Regarding the latter limitation, we did not include the coronavirus structure (including the ACE2 receptors) in this study, because many studies have already demonstrated the cellular response to this structure 19,49,50 , and how tissues that do not have significant ACE2 expression (such as neurons, immune components such as B and T lymphocytes, and macrophages) are affected by the virus remains an open question.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evidence suggests that the symptoms and signs of patients severely infected with COVID-19 are similar to the clinical phenotypes of endothelial dysfunction and have the same pathophysiological mechanism [ 6 , 14 ]. In particular, recent work by Chioh et al found that COVID-19 patients, especially those with preexisting cardiovascular risk, may show signs of persistent endothelial dysfunction even after recovery from the infection [ 15 ].…”
Section: Introductionmentioning
confidence: 99%